Steering law design for a magnetically suspended control and sensitive gyro cluster considering rotor tilt saturation. (September 2019) - Xia, Changfeng; Cai, Yuanwen; Ren, Yuan
To effectively reject the influence of rotor tilt saturation in a magnetically suspended control and sensitive gyro cluster, an adaptive nonlinear pseudo-inverse steering law is developed in this study. Based on the working principle of a Lorentz force magnetic bearing–rotor system in a single magnetically suspended control and sensitive gyro, the dynamical model of a rigid spacecraft equipped with a magnetically suspended control and sensitive gyro cluster is established. Because of the monotonicity and symmetric properties of the chosen nonlinear function, an adaptive nonlinear weighting matrix is incorporated with the pseudo-inverse steering law for the magnetically suspended control and sensitive gyro cluster. The steering law adjusts the weighting matrix elements according to saturation penalty functions so that the rotors generate control torques consistent with the limited rotor tilting domain. The effectiveness and superiority of this steering law are verified by numerical simulations. The simulation results demonstrate that the proposed steering law not only imposes control torques on the carrier spacecraft with three degrees of freedom but also avoids rotor tilt saturation, ensuring rapid attitude control of agile maneuvering spacecraft.